Pengaruh Production Cost Dan Marketing Costs Terhadap Net Profit Pada Perusahaan Sub Sektor Makanan Dan Minuman Yang Terdaftar Di BEI Tahun 2018-2020 - Ariyanto, Yuri; Hasanuh, Nanu; Sulistiyo, Hari; Suartini, Sri (Universitas Malahayati, 2024)
This study aims to determine the effect of Production Costs and Marketing Costs on Net Profit. Using quantitative methods and the population of this study are two financial statements, namely the income statement and the cost of goods manufactured report in seven listed on starting from 2018-2020 for 36 months. The analytical technique used is multiple linear analysis. The results of this study indicate that Production Cost has a negative and significant effect on Net Profit. Marketing Costs have a positive and significant effect on Net Profit. And the coefficient of determination obtained by 92% is influenced by the Independent Variable and the rest is influenced by other variables.